Fungsi Komunikasi Lintas Budaya dalam Konflik Agama Masyarakat Perbatasan Aceh - Muji Mulia; Muhajir Al-Fairusy; Zulfatmi Zulfatmi; Zakki Fuad Khalil (Aceh Anthropological Journal, 2022)
Abstract: This study discussed socio-religious events at the Aceh border. The border is defined as the boundary line between Aceh which uphold Islam as its identity with the neighboring province which has multiculturalism as its identity. The border is a melting pot for various ethnic and religious groups which formed their distinctive identity. Cross-cultural communication is become necessary to reduce religious conflict that has emerged for a long time. This study asks this question: why cross-cultural communication is important for Acehnese border communities. This study used a qualitative method with an ethnographic approach to understanding the identity awareness of people who have diverse identities. Strengthening cross-cultural communication can be categorized as a form of social engineering in the context of the integration of Acehnese border communities. The study showed that religious conflicts on the Aceh border, especially at the Singkil Regency, which have occurred since 1979 and peaked in 2015 were triggered by the state of identity politics. Religious theological nuances were massively involved in the conflict and contestation, this attitude showed the legitimacy of political interests. Historically, the people of Singkil came from one ancestor with the same clan. Community integration can only be done through culture-based communication as the glue of social relations. Cross-cultural forms of communication could be found in public spaces such as traditional markets and local community weddings.Abstrak: Studi ini mendiskusikan peristiwa sosial keagamaan di perbatasan (border) Aceh. Perbatasan mengandung makna garis batas, antara Aceh yang menjunjung Islam sebagai identitas dengan provinsi tetangga yang multikultur. Kawasan ini menjadi titik pertemuan ragam etnis dan agama yang membentuk identitas tersendiri. Komunikasi lintas budaya dalam rangka meredam konflik agama yang telah lama muncul menjadi keniscayaan. Studi ini beranjak dari pertanyaan mengapa komunikasi lintas budaya penting bagi masyarakat perbatasan Aceh. Penelitian ini menggunakan metode kualitatif dengan pendekatan etnografi untuk memahami kesadaran identitas masyarakat yang memiliki identitas beragam. Penguatan komunikasi lintas budaya dapat dikategorikan sebagai bentuk rekayasa sosial dalam konteks integrasi masyarakat perbatasan Aceh. Hasil penelitian menunjukkan jika konflik agama di perbatasan Aceh, khususnya Kabupaten Singkil yang terjadi sejak tahun 1979 dan puncaknya pada tahun 2015 dipicu oleh keadaan politik identitas. Nuansa teologis keagamaan dilibatkan secara masif dalam konflik dan kontestasi tersebut, sikap ini menunjukkan adanya legitimasi kepentingan yang bersifat politis. Realitas sejarah, masyarakat Singkil berasal dari satu nenek moyang dengan marga yang sama. Integrasi masyarakat hanya bisa dilakukan melalui komunikasi berbasis budaya sebagai perekat hubungan sosial. Bentuk komukasi lintas budaya dapat ditemui di ruang publik seperti pasar tradisional dan acara pesta perkawinan masyarakat setempat.